THE IMPORTANCE OF CULTURAL AWARENESS IN ENGLISH LANGUAGE TEACHING (Academicia Globe: Inderscience Research, 2025)
This article explores the significance of cultural awareness in English language teaching. Language is deeply connected to culture, and understanding cultural aspects enhances effective communication and comprehension. The study highlights the role of cultural elements in language learning, the challenges teachers and students face, and strategies to integrate cultural awareness into English lessons. The findings suggest that fostering cultural understanding improves learners' linguistic proficiency and intercultural competence. The article also examines the impact of globalization on language teaching and how exposure to different cultural contexts influences learners' motivation and engagement.